Dentro e fora da valise: histórias da meia noite, de Machado de Assis - Seidel, Vizette Priscila [UNESP] (2013)
This work reflects on the selection made by Machado de Assis to compose his Histórias da meia-noite. During this process, he chose certain texts that were published between 1870 and 1873, in the Jornal das Famílias, excluding a significant number of them. We researched the possible reasons for the writer’s selection, trying to observe if these choices follow any literary project of the author. In order to do so, we have examined critical readings of Machado’s works, the short stories in their medium of primary publication and theoretical references of Cultural History. We aim to contribute to the advancement of researches on Machado de Assis’ short stories, regarding the construction of these texts and configuration, by his own choice, of his literary project, as well as the possible relation between the formation of this collection and the ideal of “Brazilian literature” that the writer and critic Machado de Assis seemed to have in mind at that moment. Facts related to the history of the collection’s publication were also analyzed, in order to verify if the editor Baptiste-Louis Garnier, also the publisher of Jornal das Famílias and the collection Histórias da meia noite, of 1873, would have participated – directly or indirectly – in the selection made by the author from Rio de Janeiro